Menelusuri Makna Tersembunyi: Analisis Hambatan Komunikasi dalam Iklan IM3 'Nyatakan Silaturahmi' di Youtube melalui Perspektif Semiotika Jhon Fiske - Rahmawati, Nadya; Wiryany, Detya; Meltareza, Ridma (Communication & Social Media, 2023)
This study aims to identify and analyze communication barriers present in the IM3 "Nyatakan Silaturahmi" advertisement on YouTube, using a semiotic approach based on John Fiske's theory. This advertisement was selected for its representation of social communication phenomena within the Indonesian cultural context, which strongly values the concept of "silaturahmi" (maintaining connections). Through semiotic analysis, this research seeks to uncover hidden meanings within the ad and explore how it communicates social messages to its audience. Fiske's semiotic approach is used to highlight three levels of codes in communication: reality codes, representation codes, and ideology codes, allowing for the identification of various communication barriers in message delivery. The study results reveal communication barriers in the form of differences in perception, symbol interpretation, and cultural values presented. In conclusion, these communication barriers in the ad may affect the audience's understanding of the message, highlighting the importance of contextual and cultural considerations in conveying messages through digital media. This research is expected to provide insights into designing more effective communication strategies that are culturally sensitive and suited to diverse audiences, particularly in digital advertising.